Kepuasan Kerja Memoderasi Gaya Kepemimpinan Transformasional dan Budaya Organisasi Berbasis THK Pada Kinerja Organisasi - Ayu Pratiwi, N Kadek Lilik; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 21 No 3 (2017), 2017)
This study aimed to determine the effect of transformational leadership, organizational culture based Tri hita karana to organizational performance and job satisfaction as a moderating in the District Abiansemal LPD. Data collection method used was a questionnaire with non-probability sampling technique that includes sampling saturated and obtain 34 respondents. Data analysis technique used is the Linear Regression Analysis and Moderated Regression Analysis (MRA) to test the coefficient of determination, test the feasibility of the model and t test to test the hypothesis. The results showed that transformational leadership style has a positive effect on the performance of the organization, organizational culture based Tri hita karana positive effect on organizational performance. The job satisfaction is not able to moderate the influence of transformational leadership on organizational performance, but job satisfaction is able to moderate the influence of organizational culture Tri hita karana based on the performance of the organization.
Keywords: transformational leadership style, culture tri hita karana, job satisfaction, organizational performance.